The Legal Benefits of Islamic Rural Bank Mergers for the Banking Industry - Defilania, Oktri; Rasji (Universitas Islam Negeri Alauddin Makassar, 2026)
Mergers are a strategic tool widely used by the banking industry to ensure business sustainability, particularly in the face of capital constraints and increasing competitive risks. In the context of Sharia Rural Banks (BPRS), merger policies are not merely business-oriented but also carry significant legal implications for strengthening the structure of the national sharia banking industry. However, legal studies on the benefits of BPRS mergers tend to remain normative and have not yet been systematically analyzed based on the principle of legal utility. This study aims to analyze the legal benefits of BPRS mergers for the banking industry using a utilitarian approach, as well as to identify the legal and institutional challenges arising from the implementation of such mergers. The research method employed is normative legal research using a statutory approach and a conceptual approach. The legal materials analyzed include laws, regulations issued by the Financial Services Authority, as well as relevant legal doctrines and literature, which are subsequently analyzed qualitatively through deductive reasoning. The research results indicate that BPRS mergers provide concrete legal benefits, including strengthening capital structure, improving bank governance, enhancing the efficiency of supervision by the Financial Services Authority, and increasing customer confidence. Nevertheless, mergers also face challenges such as human resource integration, alignment of work culture, and the risk of short-term profitability decline. This study contributes to enriching the study of Islamic banking law by placing BPRS merger policies within the framework of the legal principle of utility in a more analytical and practical manner.